INVASIVENESS IDENTIFICATION: A STUDY CASE FROM LANTANA - Inggar Damayanti; Muhammad Rifqi Hariri; Melza Mulyani (Fakultas Kehutanan Universitas Jambi, 2021)
Invasion by invasive species represents one of the greatest threats to biodiversity worldwide, causing degradation and loss of habitat. Among them, one species belonged to the Verbenaceae family, namely Lantana camara, which includes 100 of the worldâ€™s worst invasive species. Distinguishing invasive from non-invasive species based on morphology alone is often difï¬cult for plants in a vegetative stage, especially in Lantana, where they have complex morphological characters. In this regard, DNA barcoding may become a good alternative. This study aimed to select and provide a DNA barcode region that capable of distinguishing the invasive and non-invasive Lantana. Four DNA Barcode markers available in the sequence database (NCBI and BOLD), namely matK, rbcL, psba-trnh, and ITS2, were used to identify the invasiveness of various Lantana. A total of 132 data sequences from 17 species of Lantana were collected. The sequences were aligned and constructed into a dendrogram using MEGA X through the Neighbor-Joining method. This study shows that it is possible to distinguish Lantana camara from a series of closely related congeners by plastid base gene (matk and rbcl). The constructed phylogeny tree shows that invasive species Lantana camara was in a different clade with non-invasive Lantana.